Perilaku Politik Masyarakat Tionghoa Dalam Pemilihan Kepala Daerah Tahun 2024 Di Kelurahan Badak Berjuang Kota Tebing Tinggi - Kapita, Kapita; Nainggolan, Mangido (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
This study aims to analyze the political behavior of the Chinese community in the 2024 Regional Head Election in Badak Berjuang Village, Tebing Tinggi City. This study is important to understand the socio-political dynamics of minority ethnic groups in the context of Indonesian democracy, exploring the factors that influence the voting behavior of the Chinese community and how cultural identity and historical experiences shape their political behavior. This study uses a qualitative method with a descriptive approach, through observation, interviews, and documentation. The subjects of the study were the Chinese community who participated in the regional elections. The results of the study show that the rational approach is the dominant factor, where the majority chooses based on realistic economic policies, support for their businesses, and the technocratic capacity of candidates. These findings indicate increasing political awareness and active participation of the Chinese community in inclusive local democracy.